Clopidogrel, prasugrel, or ticagrelor use and clinical outcome in patients with acute coronary syndrome: A nationwide long-term registry analysis from 2009 to 2014. (15th May 2017) - Sheikh Rezaei, Safoura; Geroldinger, Angelika; Heinze, Georg; Reichardt, Berthold; Wolzt, Michael
Abstract: Background: The beneficial use of dual antiplatelet therapy (DAPT) with acetylsalicylic acid (ASA) and P2Y12 õinhibitors has been established for patients after acute coronary syndrome (ACS). However, the optimal duration of DAPT is under debate. The aim of the present study was to investigate the long-term utilization and clinical outcome of clopidogrel, prasugrel, and ticagrelor in patients with ACS from 2009 to 2014 in Austria. Methods: We analysed data from 13 Austrian health insurance funds for the years 2009 to 2014, on 72, 676 patients with a hospital discharge diagnosis of ACS. The primary end point was recurrence of ACS or death > 30 days after the index event. Results: 32, 830 subjects received a prescription of a P2Y12 inhibitor within 30 days after the index ACS. 18, 640 (56.8%) subjects were discharged with clopidogrel, 6683 (20.4%) with prasugrel, and 7507 (22.9%) with ticagrelor, respectively. Data from 32, 174 patients with 4975 events during a median follow-up period of 24.9 months were available for survival analysis. The cumulative incidence for recurrence of ACS or death at two years was 18.7% in patients receiving clopidogrel, and 8.7% and 12.0% in those receiving prasugrel or ticagrelor, respectively. Conclusion: Utilization of P2Y12 inhibitors in patients with ACS was consistent with guideline recommendations . Prasugrel and ticagrelor are increasingly used in ACS patients and associated with a lower number of recurrence of ACS or death compared to clopidogrel. However, clopidogrel was predominantly used in older patients with more co-morbidities.